Itopride as an element of the management of opioid-induced constipation – preliminary results of an observational study - Dzierżanowski, Tomasz; Ciałkowska-Rysz, Aleksandra (Medycyna Paliatywna/Palliative Medicine, 2019)
It is recommended that laxatives be prescribed for the prevention of opioid-induced constipation (OIC). This retrospective study aims to verify whether itopride, added to preventive OIC therapy, decreases the necessity of regular laxatives in the prevention of opioid-induced constipation in adult palliative care patients. Ninety-two patients met the inclusion criteria. All patients received, if needed, regular laxatives, oxycodone/naloxone (OXN), itopride 50 mg TID orally, or a combination of these drugs. All methods were similarly effective in the prevention of OIC. However, the necessity of laxatives decreased in groups where itopride was used, compared to control or OXN groups (p = 0.009). OXN did not decrease laxative use (p = 0.22). We conclude that adding itopride, but not oxycodone/naloxone, resulted in a decrease in the necessity of laxative use in the prevention of OIC. Taking into consideration the limitations of this study, a randomised controlled trial is necessary to confirm this finding.